A virtual environment to emulate tailor's work. Issue 5 (29th July 2017) - Vitali, Andrea; Rizzi, Caterina
ABSTRACT: In fashion industry, 2D and 3D CAD systems to design garments already exist; however, some tasks of the process are neglected. We refer to made-to-measure garments and focus the attention on the first step of garment design, i.e. acquisition of customer's measurement. In this paper we present an application based on mixed reality, named Tailor LABoratory (TLAB), which permits to take measures for clothing design as traditionally done by the tailor. TLAB has been developed using open source libraries (e.g., VTK and Blender) and low cost devices, such as Microsoft Kinect v2 to scan the human body, Oculus Rift v2 to create the 3D virtual reality and Leap Motion device to track hands motion. In particular, a virtual tape measure is made available to take measures interacting with the human avatar. To replicate the customer's posture with her/his digital model, Blender has been adopted. It permits to manage body animations and automatic association of an animation to the 3D human avatar. Finally, preliminary tests are illustrated as well as results reached so far and future development. GRAPHICAL ABSTRACT: